Modification of the Ghosh model structure in inter-sectoral analysis - Kulyk М.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
The current Ghosh model is based on the use of value-added forecast data. The forecasts of gross domestic product and value added have long and regularly been developed by different national and international economic and financial structures, including governmental ones. The level of methods and accuracy of such forecasts is quite high as compared with the final demand forecasts on which the Leontief model is based. Therefore, from the econometric point of view, the accuracy of predictions of output made by using the Ghosh model should be at least not worse than that provided by the classical Leontief model. The modified Ghosh model formally differs from its current model by the presence of a new matrix. However, this difference is only a structural feature, and in mathematical terms these models are identical. At the same time, the modified Ghosh model is more attractive and promising than the current one due to the following factors. It uses one matrix instead of two matrices that appear in the current model. The modified model has a structure (unlike the current one) similar to the structure of the classical Leontief model. Due to this, the modified model is more understandable and easy to use. However, the most important feature lies in the fact that the use of a new matrix significantly expands the possibilities of theoretical research within the input-output structures. Due to constructing a new matrix in the modified Ghosh model, new relations between the vectors of final demand and value added were discovered, which can be efficiently used in balancing the system of input-output matrices. It was also established that the corresponding matrices of the classical Leontief model and the modified Ghosh model have identical diagonal elements in pairs, and this is useful in various analytical studies.